Social Capital, Mutual Aid and Desistance: a Theoretically Integrated Process Model - Albertson, Katherine (The British journal of criminology, 2023)
Positive social capital-building outcomes were identified in a longitudinal evaluation of a veteran-specific initiative supporting desistance from crime and substance misuse. A secondary analysis of the qualitative data generated is presented here. We identify three transformational subjective re-alignments across the veteran cohort who sustained their engagement in the mutual aid initiative. These re-alignments are linked to the mobilization of bonding, bridging and linking sources of social capital. We directly align mutual aid practice dynamics with the micro-, meso- and macro-level distinctions highlighted in relational desistance explanatory frameworks. Our analysis provides new insights into the relationship between social capital building and desistance. We present a theoretically informed social capital-building process model highlighting the generalizability of our findings to wider (ex-) offender populations.